New Economics for Sustainability - Kolozsi, Pál Péter (Public Finance Quarterly, 2023)
Gergely Baksay – György Matolcsy – Barnabás Virág (Ed.) New Sustainable Economics Global Discussion PaperMagyar Nemzeti Bank, 2022